Implikasi Need for Achievement pada Dinamika Psikologis Remaja Putus Sekolah - Beti Malia Rahma (Indonesian Journal of Humanities and Social Sciences, 2023)
This study aims to analyze the psychological dynamics of dropout adolescents and describe the implications of need for achievement on the psychology of dropout adolescents using a phenomenological approach to subjects who have completed informed consent data. Data was collected using observation techniques, interviews, FGDs, documentation, and psychological tests. Analyze by organizing data and finding patterns. Checking the validity of the data by observing and triangulating sources and techniques. The first result is that the psychological condition of the subject is reflected in the psychological dynamics of adolescents dropping out of school which appear to vary, however, the various abilities of the subject tend to be low and need guidance and direction, especially to organize the future. The psychological dynamics of the subject can be seen from the cognitive, affective, and conative aspects which still have a dominant tendency to lack or weakness. Second, subjects who work or not tend to have a picture of psychological dynamics with low ability and personality aspects and a lack of need for achievement. It takes more effort and requires support from various parties to be able to achieve welfare in the future.